(untitled) (De Rebus Antiquis, 2020)
Fear is commonly regarded as a natural emotion in war, present as well in ancient Greek warfare. Greek literary sources occasionally emphasize the emotions connected to the contemporary experience of combat from a primarily narrative perspective. This paper will offer an introduction to the Greek notion and conceptualization of fear in the classical period and its relationship with war, intending to achieve a better understanding of its role in the literary sources and, ultimately, its relevance in Greek culture and warfare.